German Free Churches and the Nazi Regime - Railton, Nicholas (The journal of ecclesiastical history, 1998)
There are a number of excellent studies on the Protestant Churches in the Third Reich, but none contains a thorough treatment of the smaller Free Churches. Ernst Christian Helmreich included a short chapter on these in his 1979 work on The German Churches under Hitler: background, struggle and epilogue. The recent publication of a work by Andrea Strübind on the German Baptist Churches, Die unfreie Freikirche: der Bund der Baptistengemeinden im Dritten Reich (1995), and by Herbert Strahm on the Episcopal Methodist Church, Die Bischöfliche Methodistenkirche im Dritten Reich (1989), should encourage research on a topic that has been badly neglected in the past.This article seeks to shed light on the relationship of German evangelicalism as embodied in the Free Churches to the mainline provincial churches as well as to the regime of National Socialism. It will show that evangelicals were actually far less united than is generally perceived to be the case.